The Personal Selling and Sales Management Ethics Research: Managerial Implications and Research Directions from a Comprehensive Review of the Empirical Literature - McClaren, Nicholas (2013)
Research into ethics in personal selling and sales management has increased substantially over the preceding decade by investigating complex dimensions of ethical decision-making in greater depth and with more analytical sophistication. This review of the recent conceptual and empirical literature provides insight into the extent and the direction of this knowledge, recommends managerial action, and discusses areas for future exploration. Future direction is also provided through research propositions. The type of sales practitioner investigated, the main variables examined, and the key findings are summarized in an Appendix.
Keywords: Personal Selling; Marketing; Management; Sales; Literature; Ethics; Empirical; Review